The influence of cavity mold making technology on the efficiency of plastics processing - Pepliński, K. (Polimery, 2021)
The influence of injection mold manufacturing methods – cutting (CM) and additive (AM) – on the quality of obtained molds and parts produced from them, processing efficiency and harmfulness of environmental impact of the products and mold making/plastic processing methods was investigated. The assessment was made on the basis of the indicator values for postulated states corresponding to the mathematical models of the economic, energy and ecological process efficiency as well as the environmental harmfulness of the product and plastic processing method based on experimental research under real conditions.